Potensi Formulasi Sediaan Sabun Padat Minyak Kelapa dengan Pengisi Bentonit sebagai Media Pembersih Najis Mughallazah - Tobing, Maria Grace; Sukeksi, Lilis; Iriany; Siswarni (Talenta Publisher (Universitas Sumatera Utara), 2021)
Najis mughallazah is excrement which comes from pigs which earthen soap can use to purify it.Â Method to purify unclean that is necessary to use water seven times and the addition of bentonite to soap is expected to be able to remove unclean Deoxyribonucleic Acid (DNA) that is located on the surface of human skin. The purpose of this study was to determine the effect of the amount of bentonite filler and the reaction temperature on the quality of soap, knowing whether the soap formula meets the SNI quality requirements and knowing whether the soap formula can remove Pig DNA residues using the Polymerase Chain Reaction (PCR) analytical method. In this study, the operation conditions were designed at the reaction temperature (50 oC, 60 oC, 70 oC and 80 oC), bentonite consistency (10%, 12.5%, 15%, 17.5% and 20%), 35% NaOH concentration, reaction time 10 minutes and stirring speed 250 rpm. The analyzes carried out in this study include analysis of water content, free alkaline content, free fatty acid content and PCR method. The best results were obtained for 15% (70 Â°C) soap that had soap hardness characteristics close to conventional soap and 17.5% (50 Â°C) soap with the characteristics of soap that could remove najis mughallazah. The resulting solid bentonite soap formula meets the SNI 3523: 2016 standard and can eliminate mughallazah unclean.